Analisis Pendapatan Usahatani Karet Rakyat - Nursamsi Nursamsi (JASc (Journal of Agribusiness Sciences), 2018)
This research was conducted with the aim to determine the income of smallholder rubber farming. The population in this study was smallholder rubber farmers in Mahato Village, North Tambusai District, Rokan Hulu Regency. From the results of the study obtained the amount of smallholder rubber production of 7333.32 kg at a price of Rp. 7,700 / Kg, the total farmer income is Rp. 56,512,764 per year. Total costs incurred in the amount of Rp. 34,330,565 per year, so that an income of Rp. 22,182,199. Smallholder rubber farming is feasible to be cultivated based on NPV, IRR, Net B / C and PBP criteria with NPV value of 22,457,830, IRR value of 16.67%, Net B / C of 1.44 and PBP value of 15.9 Months